Evaluating Prospective Teachers: Testing the Predictive Validity of the edTPA - Goldhaber, Dan; Cowan, James; Theobald, Roddy (Journal of teacher education, 2017)
We use longitudinal data from Washington State to provide estimates of the extent to which performance on the edTPA, a performance-based, subject-specific assessment of teacher candidates, is predictive of the likelihood of employment in the teacher workforce and value-added measures of teacher effectiveness. While edTPA scores are highly predictive of employment in the state’s public teaching workforce, evidence on the relationship between edTPA scores and teaching effectiveness is more mixed. Specifically, continuous edTPA scores are a significant predictor of student mathematics achievement in some specifications, but when we consider that the edTPA is a binary screen of teaching effectiveness (i.e., pass/fail), we find that passing the edTPA is significantly predictive of teacher effectiveness in reading but not in mathematics. We also find that Hispanic candidates in Washington were more than 3 times more likely to fail the edTPA after it became consequential in the state than non-Hispanic White candidates.